Arthropod Diversity in the Tea Plantation within Several Years after Pruning in Pagilaran, Central Java - Muhammad Rizyan Anggra Hidayat; F. X. Wagiman; Arman Wijonarko (Jurnal Perlindungan Tanaman Indonesia, 2019)
The lush leaves of tea within several years after prune is expected to be followed by arthropod abundance and diversity. The study aimed to evaluate the arthropod abundance, diversity, evenness, and dominance, at the tea plantation within several years after the prune. The study was conducted at Pagilaran tea plantations, Central Java, from April to May 2018, at an altitude of 900 m asl. Arthropod samplings were done in four plots of tea plantation namely 1, 2, 3, and 4 years after pruning, hereafter they are called PY1, PY2, PY3, and PY4.  The plot area was approximately 1 ha. The arthropod specimens were collected using sweep net and pitfall trap every day for 6 consecutive days.  The arthropod identification and calculation were carried out in the Laboratory of Entomology, Faculty of Agriculture, Universitas Gadjah Mada. Analysis of variance was applied to determine the effect of PY on the Arthropod abundance. The Shannon Wienner index, the Evenness index, and the Simpson index, were used to evaluate the arthropod diversity, evenness, and dominance, respectively. The results showed that the PY significantly affected the arthropod abundance. The arthropod number collected from PY1 (27 individuals/50 swings) was significantly lower as compared to the other PYs, while arthropod numbers amongst PY2, PY3, and PY4 (53, 93, and 67 individuals/50 swings, respectively) were relatively similar. Out of the total number of 1.432 arthropod specimens, it comprised of 10 orders at which Hemiptera was the highest order (48.04%), and 69 families at which Cicadellidae was the highest family (32.12%). Amongst specimens of Cicadellidae, there was Empoasca sp. which is an important tea pest. The Shannon Wienner index (H) of orders and families ranged from 1.24 to 2.69 indicates moderate arthropod diversity. The Evenness index (e') ranged from 0.57 to 0.91) indicates the arthropod evenly distributed. Meanwhile, the Simpson index (D) ranged 0.10 - 0.39 indicates that there was no dominance of the order or family.